1978
DOI: 10.1111/j.1432-1033.1978.tb12542.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quenching and Energy Transfer in Complexes between Horse‐Liver Alcohol Dehydrogenase and Coenzymes

Abstract: The fluorescence properties of horse-liver alcohol dehydrogenase were investigated with the aim of separating the contribution of Trp-15 (which is close to the protein surface) from that of Trp-314 (buried in the interior of the protein). Quenching of the protein fluorescence by iodide involves, to a larger degree, the longer wavelength region of the protein emission spectrum and is interpreted to involve only , , at 340 nm and a quantum yield of 0.19). It is shown that quenching by NAD and NADH involves bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

1983
1983
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 38 publications
3
26
1
Order By: Relevance
“…Since each of the two enzyme subunits contains one hydrophilic (residue 15) and one hydrophobic (residue 314) tryptophan [16,17], it is possible to state that the longer-wavelength component belongs to Trp-I 5, and the shorter-wavelength one relates to Trp-314. The results obtained are consistent with those of others [8,9,11,12]. Barboy and Feitelson [lo] suggested that 300-nm light excites only Trp-314.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Since each of the two enzyme subunits contains one hydrophilic (residue 15) and one hydrophobic (residue 314) tryptophan [16,17], it is possible to state that the longer-wavelength component belongs to Trp-I 5, and the shorter-wavelength one relates to Trp-314. The results obtained are consistent with those of others [8,9,11,12]. Barboy and Feitelson [lo] suggested that 300-nm light excites only Trp-314.…”
supporting
confidence: 83%
“…This finding is not It should be noted that in various works the value of maximal quenching of alcohol dehydrogenase luminescence upon NAD' addition was found to be different. Thus, in [l] it was equal to 20%, in [2] it amounted to 42%, in [5] 47%, in [12] 28%. This is not connected with differences in the experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2 shows the emission spectra of tubulin (I), tubulin-colchicine complex (11) and the difference sprectra (111), when excited at 295 nm. The emission maximum of the free protein (I) is at 336.8 nm.…”
Section: Wave Length (Nm)mentioning
confidence: 99%
“…These estimates are significantly shorter than the NADH-TrplS distances, which are 3.6 nm and 5.2 nm, and significantly longer than the NADHTrp314 distances, which are 1.7 nm and 2.4 nm (from X-ray crystal structure data of the NADH-dimethyl sulphoxide-LADH ternary complex ; [I 41) supporting the idea of a binding site distinct from the coenzyme-binding site. Although the specificities of the interaction of colchicine and colcemid with tubulin are compared with that of the enzymesubstrate interaction, it was reported that colchicine and colcemid bind glyceraldehyde-3-phosphate dehydrogenase with Kd values of M and 6X10-'M [18], respectively. Thus, it would be interesting to see whether dehydrogenases possess the general property of binding colchicine and its analogs.…”
Section: Resultsmentioning
confidence: 99%